The Name of the Prophet Muhammad (PBUH), A Contextual Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Prophet was mentioned by his name Muhammad four times in the Holy Qur’an and in his name (Ahmad) once. The mention of these two noble names was accompanied by a steady and clear speech about jihad, and mujahideen, and the Prophet’s invasions, indicating that this religion must have strength to protect it in order for its message to reach as a mercy to both worlds.